THE EFFECT OF AMOXICILLINE AND AMOXICILLINE + OMEPRAZOL ON ULCER HEALING AND ERADICATION OF H-PYLORI - Ali Reşit BEYLER,; Ali GÖREN,; Ali ÖZDEN,; Kazım SOYLU,; Ş. Erol KESİM,; Murat PALABIYIKOĞLU,; Hülya ÇETİNKAYA,; Hakan BOZKAYA,; Özden UZUNALİMOĞLU, (Turkish Journal of Gastroenterology, 2020)
-